Pengembangan E-LKPD Berbasis Problem Based Learning Untuk meningkatkan Kemampuan Pengambilan Keputusan Peserta Didik - Ismawati, Eka Yulianda; Khoiri, Nur; Saefan, Joko; Ristanto, Sigit; Prakosa, Hafizh Aji; Ristianti, Sinta (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
21st Century Learning is learning that demands the development of more interesting learning media and utilizing technology. But in fact, the use of technology in the learning process is still not utilized optimally. For this reason, this research was motivated by the lack of use of technology in learning media used in the classroom. The purpose of this study is to develop learning media in the form of E-LKPD based on Problem Based Learning on learning that can be used to improve students' decision-making abilities. The development model used is the ADDIE development model. The research instruments used are expert validation sheets to measure the feasibility of E-LKPD and pretest postest questions to measure students' decision-making abilities. The results of E-LKPD eligibility validation by material experts and media experts obtained percentages of 96.875% and 92.30%. The results of the learners' pretest postest were tested with the T test and obtained a significance of 0.000. Based on the results of the overall research, E-LKPD is feasible to be used as a learning medium to improve the decision-making ability of students.